2020
DOI: 10.5812/ijpbs.87974
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Persian Version of Personality Inventory for DSM-5 (PID-5) in Psychiatric Patients

Abstract: Background: The fundamental problems with the personality disorders diagnostic system in DSM-IV led to the revision of the DSM approach and proposition of a dimensional model for DSM-5. The DSM-5 Personality and personality disorders workgroup developed the personality inventory for DSM-5 (PID-5) to assess the pathological personality traits within this new model. Objectives: The purpose of this study was to investigate the psychometric properties of PID-5 in psychiatric patients. Methods: In a cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Regardless of scoring algorithms for the maladaptive domains, items response is based on a Likert scale ranging from 0 ( often false ) to 3 ( often true ). The reliability and validity of the Persian version of PID‐5 are acceptable in the Iranian populations (Amini et al, 2021; Hemmati et al, 2021; Lotfi et al, 2018; Shojaei et al, 2020). In the present sample, Cronbach's ⍺ for all domains of both DSM‐5/ICD‐11 systems and DSM‐5 PD composites were acceptable, ranging from 0.84 to 0.96.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regardless of scoring algorithms for the maladaptive domains, items response is based on a Likert scale ranging from 0 ( often false ) to 3 ( often true ). The reliability and validity of the Persian version of PID‐5 are acceptable in the Iranian populations (Amini et al, 2021; Hemmati et al, 2021; Lotfi et al, 2018; Shojaei et al, 2020). In the present sample, Cronbach's ⍺ for all domains of both DSM‐5/ICD‐11 systems and DSM‐5 PD composites were acceptable, ranging from 0.84 to 0.96.…”
Section: Methodsmentioning
confidence: 99%
“…Although the cross-cultural reports support the validity of all versions of PID-5 (Al-Dajani et al, 2016;Amini et al, 2021;Bagby et al, 2022;Bo et al, 2016;Coelho et al, 2020;Fang et al, 2021;Hemmati et al, 2021;Hong et al, 2018;Sellbom et al, 2020;Shojaei et al, 2020;Thimm et al, 2016;Venema et al, 2021;Zhang et al, 2021), a few studies focused on determining the cut points of the scale to diagnose clinical status (Bagby & Sellbom, 2018;Keeley et al, 2014). The neglect by previous studies may be affected by the dimensional approach to measurement that underlies the PID-5 structure (Waugh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many studies based on factor analytical techniques that form the basis of the HiTOP system are inattentive to the etiology of personality and psychopathology, other studies have attempted to extract common factors between traits developed using factor analysis and those in temperamental theories. [35][36][37] For example, Clark and Ro 35 found that high HA and internalizing spectrum traits in the HiTOP loaded on a common higher-order factor they called negative affectivity. Also, of all the traits examined, high NS had its highest factor loading on a disinhibited externalizing spectrum and low RD on the detachment spectrum.…”
mentioning
confidence: 99%